An order tracking system in dynamic virtual enterprise based on SaaS and web service. (1st January 2013) - Jiang, Jianhua; Zuo, Ying; Zhang, Yue
Dynamic virtual enterprise (DVE) takes outsourcing as the main business mode and it allocates customer orders to appropriate suppliers by bidding or negotiation. The real-time query of the implementation status of orders is named order tracking. Provide order tracking service in DVE helps customers to participate in the manufacturing process of their orders so to improve their loyalty to DVE. The service is also benefit for the core enterprise of DVE to reallocate order in suppliers to ensure the timely completion of orders and help suppliers to query the progress of tasks in its upstream enterprises. To achieve the order tracking of cross-enterprises and provide web-based order tracking service in DVE, a SaaS and web service-based order tracking platform was put forward. To realise the platform, the SaaS-based manufacturing data management system was constructed, and the packaging method of application system into web service was researched. Then the process of order tracking in the platform was designed and the order tracking service based on web was realised. Finally, the feasibility of the platform was verified by the development of a prototype system.